The Molecular Basis for the Mode of Action of Bicyclomycin - Kohn, Harold; Widger, William (Current Drug Targets - Infectious Disorders, 2005)
Bicyclomycin (1) is a clinically useful antibiotic exhibiting activity against a broad spectrum of Gram-negative bacteria and against the Gram-positive bacterium, Micrococcus luteus. Bicyclomycin has been used to treat diarrhea in humans and bacterial diarrhea in calves and pigs and is marketed by Fujisawa (Osaka, Japan) under the trade name Bicozamycin. The structure of 1 is unique among antibiotics, and our studies document that its mechanism of action is novel. Early mechanistic proposals suggested that 1 reacted with nucleophiles (e.g., a protein sulfhydryl group) necessary for the remodeling the peptidoglycan assembly within the bacterial cell wall. We, however, showed that 1 targeted the rho transcription termination factor in Escherichia coli. The rho protein is integral to the expression of many gene products in E. coli and other Gram-negative bacteria, and without rho the cell losses viability. Rho is a member of the RecA-type ATPase class of enzymes that use nucleotide contacts to couple oligonucleotide translocation to ATP hydrolysis. Bicyclomycin is the only known selective inhibitor of rho. In this article, we integrate the evidence obtained from bicyclomycin structure-activity studies, site-directed mutagenesis investigations, bicyclomycin affinity labels, and biochemical and biophysical measurements with recent X-ray crystallographic images of the bicyclomycin-rho complex to define the rho antibiotic binding site and to document the pathway for rho inhibition by 1. Together, the structural and functional studies demonstrate how 1, a modest rho inhibitor, can disrupt the rho molecular machinery thereby leading to a catastrophic effect caused by the untimely overproduction of proteins not normally expressed constitutively, thus leading to a toxic effect on the cells.
Keywords: rho